A questão da técnica em Heidegger - Cocco, Ricardo (Universidade do Vale do Rio do Sinos, 2007)
In this dissertation is intended to present some aspects about the origin and the unfolding on the question of technique in Martin Heidegger’s philosophy. The development of the dissertation begins by presenting the background on the case of technique: the criticism to the traditional metaphysics as explained in Being and Time and the criticism about the modern science as it has been showed in Contributions to Philosophy: about the happening in order to understand the essential view of the question about the technique in the Philosopher’s thought. It goes on demonstrating how much and how Heidegger’s ideas, already outlined in his writings on the second half of the thirties, have a certain basis in Ernest Jünger’s ideas. Next, the text explains the Heideggerian understanding in the point of view of the essence of the modern technique as a non-personal device that leads everything away (Gestell’s notion). At last, it is rendered evident the alternative that has been suggested by Heidegger in relation to the ri
Keywords: crítica; técnica; Heidegger, Martin; metafísica; Ciências Humanas